School-Based Peer Group Support as a Psychosocial Strategy to Promote Mental Health in Adolescents: A Quasi-Experimental Approach - Zahran Nurfadhilah Solihudin; Angga Saeful Rahmat; Surandi Ketaren (STIKep PPNI Jawa Barat, 2025)
Background: Adolescents are vulnerable to psychological distress due to rapid developmental changes and social pressures. School-based psychosocial strategies such as peer group support may enhance early mental-health promotion. Objective: To evaluate the effectiveness of peer group support on mental health indicators among junior high school students. Methods: A quasi-experimental pretest–posttest control group design was conducted among 84 adolescents aged 12–15 years at SMPN 4 Klari, Karawang Regency, Indonesia. The intervention group received 8 peer-support sessions across 8 weeks. Mental health was assessed using the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using paired and independent t-tests and ANCOVA. Results: The intervention significantly improved adaptive coping (+42.4%), reduced stress symptoms (−35.8%), and increased health-maintenance behaviors (+43.1%). Between-group post-intervention differences were statistically significant (p < .001). Effect size analysis indicated a large treatment impact (Cohen’s d > 0.8). Conclusion: Peer group support effectively enhances adolescent mental health and coping abilities. Integrating peer-based interventions into school programs is recommended to foster a supportive psychosocial environment.